2017
DOI: 10.15537/smj.2017.5.17936
|View full text |Cite
|
Sign up to set email alerts
|

Primary care physicians’ knowledge of sleep medicine and barriers to transfer of patients with sleep disorders

Abstract: Objectives:To assess primary care physicians’ (PCPs) knowledge and attitudes toward sleep disorders.Methods:In this cross-sectional quantitative study, we surveyed 88 primary care centers under the Ministry of Health during 2015 in Riyadh, Saudi Arabia, using a combination of pre-designed validated questionnaires. Knowledge was assessed using the Assessment of Sleep Knowledge in Medical Education (ASKME) questionnaire, and attitude was assessed using a pre-designed survey. For numerical variables, t-test was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 16 publications
0
17
1
Order By: Relevance
“…Two surveys have shown that primary care physicians' knowledge regarding sleep disorders is limited. 31,32 The lack of education regarding sleep medicine has resulted in a culture of physicians who have a limited knowledge about sleep disorders; therefore, they are likely to underdiagnose and undertreat sleep disorders. Several local studies highlighted the underrecognition of sleep disorders among Saudi health care providers.…”
Section: Knowledge Of Medical Students and Health Care Workers Regardmentioning
confidence: 99%
“…Two surveys have shown that primary care physicians' knowledge regarding sleep disorders is limited. 31,32 The lack of education regarding sleep medicine has resulted in a culture of physicians who have a limited knowledge about sleep disorders; therefore, they are likely to underdiagnose and undertreat sleep disorders. Several local studies highlighted the underrecognition of sleep disorders among Saudi health care providers.…”
Section: Knowledge Of Medical Students and Health Care Workers Regardmentioning
confidence: 99%
“…In Croatia [21], among 112 respondents surveyed, poor knowledge of sleep issues was identified in most of the medical students, postgraduate physicians and specialists, which corroborates our results. In another study published locally (in the KSA), Saleem et al [14] surveyed 88 primary care centres comprising 223 primary care physicians (PCP). They reported that the mean knowledge of PCP based on the ASKME questionnaire was 14.4 (± 4).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the knowledge of practising physicians, particularly primary care physicians, about sleep disorders is limited [13]. Salem et al reported that only 33.6% of the primary care physicians assessed knew sleep medicine [14]. A survey of primary health care (PHC) physicians in all primary care centres in Riyadh revealed that PHC physicians do not completely recognise the importance and impact of OSA and other sleep disorders [13].…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of insomnia among primary health-care visitors necessitates adequate awareness of insomnia among primary health-care providers. Unfortunately, recent studies indicated that awareness about sleep disorders among health-care givers in some countries still poor (Bhaskar et al 2016;Saleem et al 2017). Poor awareness of health-care givers together with a low reporting rate of the sufferer to physicians makes the problem of insomnia underestimated and undertreated (Leger and Poursain 2005).…”
Section: Discussionmentioning
confidence: 99%